New approach to improve the distortional strength of intermediate length cold formed steel rack columns - Anbarasu, M.; Kumar, S. Bharath; Sukumar, S. (Journal of Structural Engineering, 2024)
This article presents a new approach to improve the torsional stiffness and also distortional strength of cold-formed steel rack columns by adding the spacers externally. The aim is to evaluate the efficiency of this method by comparing the behaviour of open section, fully closed section and with spacer. In this work two types of sections were considered Type-I section with lip projecting outwards (hat) and Type-II section with lip projecting inwards (channel). Axially loaded eight columns were tested with hinged-hinged end condition. The length of the columns was predicted by performing elastic buckling analysis using CUFSM software. Numerical analysis was performed using ANSYS for establishing the influence of the provision of spacers on the behaviour and ultimate load. Experimental results were verified with finite element analysis results. After the verification of the finite element model extensive parametric study was carried out by varying the depth and interval of spacers by using this numerical finite element procedure. Results of experimental and numerical analysis of two types of open sections were compared with theoretical analysis using DS M - S100:2007, AS/NZ: 4600- 2005 and IS: 801-1975. Based on the nonlinear regression analysis the design equations are proposed for both types of columns.